2023
DOI: 10.2196/42965
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of a Text-Based Conversational Agent for Asthma Support: Protocol for a Mixed Methods Observational Study

Abstract: Background Despite efforts, the UK death rate from asthma is the highest in Europe, and 65% of people with asthma in the United Kingdom do not receive the professional care they are entitled to. Experts have recommended the use of digital innovations to help address the issues of poor outcomes and lack of care access. An automated SMS text messaging–based conversational agent (ie, chatbot) created to provide access to asthma support in a familiar format via a mobile phone has the potential to help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…According to our findings, they are already in the focus of urological symptom checking, health screening, patient education, counseling, lifestyle change, conservative management, clinical decision support, and post-treatment follow-up care. The same was shown by Calvo et al [ 29 ], who conducted a study on the feasibility and usability of a text-based conversational agent that processes a patient’s text responses and short voice recordings to calculate an estimate of their risk for an asthma exacerbation. The chatbot offers follow-up information for lowering risk and improving asthma control, to improve understanding and self-management of the condition.…”
Section: Discussionmentioning
confidence: 62%
“…According to our findings, they are already in the focus of urological symptom checking, health screening, patient education, counseling, lifestyle change, conservative management, clinical decision support, and post-treatment follow-up care. The same was shown by Calvo et al [ 29 ], who conducted a study on the feasibility and usability of a text-based conversational agent that processes a patient’s text responses and short voice recordings to calculate an estimate of their risk for an asthma exacerbation. The chatbot offers follow-up information for lowering risk and improving asthma control, to improve understanding and self-management of the condition.…”
Section: Discussionmentioning
confidence: 62%
“…Some studies (4/43, 9%) used the System Usability Scale questionnaire to measure the system’s usability score and predominantly found high usability, with System Usability Scale scores of >70 [ 72 - 75 ]. Alternatively, multiple studies (10/43, 23%) used the subjective ratings of most of the participants to evaluate the feasibility and acceptability of CAs by applying indicators such as perceived usefulness [ 76 - 79 ], ease of use [ 78 , 80 ], user satisfaction [ 80 , 81 ], engagement rate [ 80 , 82 , 83 ], perceived closeness [ 73 ], and Net Promoter Score [ 84 ]. However, 2% (1/43) of the studies reported negative usability and acceptability outcomes, indicating unsatisfactory reliability, usability, and goal structure, which hindered health care professionals’ acceptance and trust [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…An initial protocol paper outlined a study plan for developing and evaluating the feasibility of a chatbot designed to assist patients with asthma with risk self-assessment and self-management. 21 The user research and co-design phase of the project, which involved respiratory specialist physicians, asthma nurses, representatives from an asthma advocacy organisation and asthma patients, is described in Moradbakhti et al 22…”
Section: Methodsmentioning
confidence: 99%